Hubungan Dukungan dan Pengetahuan Orang Tua dengan Motivasi Berkhitan Siswa MIS Amal Shaleh Perumnas Simalingkar Medan di Masa Pandemi Covid-19 - Erika Erika; Wina Viqa Sari (LPPM STIKes Indah Medan, 2021)
During the Covid-19 pandemic, people in Medan experienced anxiety. This is indicated by the community's low interest in circumcising their children, which is seen from the number of circumcision participants carried out by the Indah Foundation at the Indah Medan College of Health Sciences in 2020, in January with only 12 participants, 9 (June), 15 (October). Likewise on Radio Indah Suara 96.5 FM Perbaungan in December 2019 with 11 people, in June 2020 with 14 people, in October with 15 participants. This paper aims to determine the relationship between parent's support and knowledge for motivating their children to do circumcision. The method is done by looking at the correlation between parent's support and knowledge with the motivation to circumcise the child and seeing how multiple (simultaneous) correlation between the support and knowledge of parents and the motivation to circumcise the child. The author can conclude that the majority of students' parents (55%) do not support their children being circumcised during the Covid-19 pandemic, and parents' knowledge of circumcision during the Covid-19 pandemic is still inadequate, seen from the level of understanding of parents regarding circumcision during the Covid-19 pandemic is at a moderate level (66.67%).